(untitled) (Journal of Engineering, 2013)
Irrigation scheduling techniques is one of the suggested solutions for water scarcity problem. The study aims to show the possibility of using practical and applicable irrigation scheduling program which was designed by Water Resources Department at the University of Baghdad by using Spreadsheet Formulas for Microsoft Excel program, version 2007, with some modification to generalize it and made it applicable to various climatic zone and different soil types, as a salvation for the shortage of irrigation water inside the irrigation projects. Irrigation projects which incidence of Tigris River basin will be taken as an applicable example. This program was based on water budgeting and programmed depending on scientific concepts which facilitate irrigation structures operation and ease the use by farmers. By using the abilities of this program, the monthly and annually water requirements and drainage water were estimated. Finally a comparison is made between the calculated discharges with the designers suggested ones. This comparisons showed that the use of this type of irrigation scheduling (i.e. predicted irrigation scheduling) with itsapplicable constrains require high attention when choosing the cropping pattern for each climate zone. Also it found that this irrigation program is a useful tool for saving water if cropping pattern has been chosen carefully.